PENGARUH MEDIA BONEKA TANGAN TERHADAP KETERAMPILAN MENYIMAK CERITA SISWA KELAS III SD NEGERI PAGENDISAN PATI - Andriyati, Dwi Desi; S.D., Endah Rita; Kiswoyo, Kiswoyo (JURNAL SINEKTIK, 2020)
The purpose of this study was to determine the effect of using hand puppet media on listening skills to the stories of third grade students of SD Negeri Pagendisan Pati. The type of research used in this study is quantitative and pre-experimental design with the type of One Group Pretest-Posttest Design. This study uses a saturated sampling technique that is according to third grade students. While the data collection techniques used are tests, interviews, and documentation. Student learning outcomes in this study obtained an average pretest value was 52.65 and an increase in the average posttest score was 79.12. The results of the study concluded that class III of Pagendisan State Elementary School was normally distributed because Ltable = 0.195> Lhitung = 0.117, the initial data were normally distributed.